Computer simulation investigation on the effect of channelled and unchannelled screens on smoke contamination in atriums upper Balconies - Nasif, M.S. (EDP Sciences, 2014)
This paper performed the effect of installing channel screen on smoke contamination in the presence of 0.5 m deep down stand in a fire compartment. The results are then compared with smoke contamination occurrence when the channel screens were removed. The results showed that there will be 96 increase in upper balconies smoke contamination in an atrium when no channel screens at fire compartment opening are used. This work provides new correlation obtained from numerical study which can predict the smoke contamination height in upper balconies of the atrium in the presence of 0.5 m down stand and no channel screens. The proposed correlation will be useful design tool for building designer to design safe shopping malls (atrium). Â© 2014 Owned by the authors, published by EDP Sciences.